Uji Adaptasi dan Validasi Sosial Media Fatigue Scale Versi Bahasa Indonesia - Eko Sudrajat; Febrio Hasta Pratama; Septian Odie Saputra; Luvy Maydelar; Syarah Nadiva; Citra Epina Indatirani (CV. PUSDIKRA MITRA JAYA, 2026)
Social Media Fatigue (SMF) is a negative psychological consequence of excessive social media use, characterized by feelings of being overwhelmed, frustration, and the desire to withdraw. Valid instruments for measuring this construct within the Indonesian context remain limited. This study aims to adapt and examine the validity and reliability of the Indonesian version of the Social Media Fatigue Scale (SMFS) among emerging adults. This instrumental study involved active social media users aged eighteen to thirty nine years. The adaptation process followed International Test Commission guidelines, including forward backward translation, expert review, and readability testing. Construct validity was tested using Exploratory Factor Analysis and Confirmatory Factor Analysis. Reliability was estimated using Cronbach Alpha coefficients. Exploratory Factor Analysis yielded a three factor structure that differed from the original model. Confirmatory Factor Analysis indicated that the three factor model did not achieve adequate goodness of fit. Reliability analysis revealed low to moderate internal consistency. The findings suggest that the Indonesian version of SMFS lacks adequate construct validity and reliability, highlighting the need for cultural adaptation or development of an indigenous instrument to measure social media fatigue in Indonesia.